Merovingian mortuary archaeology and the making of the early Middle Ages - Effros, Bonnie, 1965- (Transformation of the classical heritage, 2003)
Clothing, jewellery, animal remains, coins and weaponry are among the artifacts that have been discovered in graves in Gaul dating from the fifth to the eighth centuries. This text traces the history of Merovingian mortuary archaeology within its cultural and intellectual contexts.